Linguistic Decision Making Numerical Scale Model and Consistency-Driven Methodology - Dong, Yucheng; Xu, Jiuping (Springer Nature Singapore : Imprint: Springer, 2019)
This book proposes a novel CWW model to personalize individual semantics in linguistic decision making, based on two new concepts: numerical scale and consistency-driven methodology. The numerical scale model provides a unified framework to connect different linguistic symbolic computational models for CWW, and the consistency-driven methodology customizes individuals' semantics to support linguistic group decision making by setting personalized numerical scales. The book is a valuable resource for researchers and postgraduates who are interested in CWW in linguistic decision making.